(untitled) (World Economics and Finance Bulletin, 2025)
The research purposes to clarify the role of dimension and accounting disclosure of social responsibility in meeting the requirements of stakeholders and rationalizing their decisions, by identifying the theoretical framework for measurement and secretarial disclosure of social responsibility and indicating the possibility of its application in the Iraqi economic units in order to help determine the extent of commitment of these units to their social responsibilities and meet the requirements of the environment and society in general. The research was applied in Al-Furat State Company for Chemical Industries, which is one of the public companies affiliated with the Iraqi Ministry of Industry and Minerals, and the research was applied in the company’s research sample for the period from 2021 to 2024. Several conclusions were reached, the most important of which was that the outputs of the current accounting systems fall short of disclosing the costs of social responsibility and the extent of social benefits that it causes in the society in which it operates, and with the emergence of the modern trend in looking at the facility as part of a society affected and affected by the introduction of accounting thought accounting system for social responsibility due to the development and complexity of various economic activities and increase their impact on the environment.